Implikasi Paham Komunisme dalam Kehidupan Bernegara - Gilang Rizki Aji Putra (ADALAH, 2019)
Abstract:Communist ideology that can be used as a comparison to see the weaknesses and weaknesses of other ideologies. A tired communist is a communist in the sense of a non-communist idea or thought in the sense that a radical communist puts forward the ideology of power by putting forward the revolutionary procedure for power. Communists are also an inseparable part of the hustle and bustle of world life. in the power of ideology as an attachment which is always perpetuated and a practice that cannot be abandoned or even bargained with. Idiology is the key to various kinds of movements that lead to being overwhelmed. A little bit of this paper tries to describe the understanding of communism in the historical frame and the ideology of power that can enrich intellectual treasures in the world of science.Keywords: Communism, Idiology, and Karl MarxAbstrak:Idiologi komunis yang dapat dijadikan sebagai perbandingan pada melihat kekurangan serta kelemahan idiologi yanglainnya. Komunisyang capek merupakan komunis pada  artian sebuah paham atau pemikiran bukan komunis pada artian komunis radikal yg mengedepankan idiologi kekuasaan dengan mengedepankan tatacara revolusi buatsebuah kekuasaan. Komunis pun bagian yang tak terpisahkan berasal hirukpikuk kehidupan dunia. dalam kekuasaan penguasaan idiologi sebagai pelekat yang selalu dilanggengkan dan  amaliah yang takboleh ditinggal bahkan ditawar-tawar. Idiologimenjadi kunci aneka macam gerakan yang berujung dikekusaan. Sekelumittulisan ini berusaha mendeskripsikan pemahaman perihal komunisme dalam bingkai sejarah serta idiologi kekuasaan yang dapat memperkaya khazanah intelektual dalam dunia ilmu pengetahuan.Kata Kunci: Komunisme, Idiologi, dan Karl Marx